Tailoring P2/P3 Biphases of Layered NaxMnO2 by Co Substitution for High‐Performance Sodium‐Ion Battery. Issue 7 (27th January 2021) - Jiang, Na; Liu, Qiunan; Wang, Jiawei; Yang, Wanfeng; Ma, Wensheng; Zhang, Liqiang; Peng, Zhangquan; Zhang, Zhonghua
Abstract: P‐type layered oxide is a promising cathode candidate for sodium‐ion batteries (SIBs), but faces the challenge of simultaneously realizing high rate capability and long cycle life. Herein, Co‐substituted Na x MnO2 nanosheets with tunable P2/P3 biphase structures are synthesized by a novel dealloying–annealing strategy. The optimized P2/P3–Na0.67 Mn0.64 Co0.30 Al0.06 O2 cathode delivers an excellent rate capability of 83 mA h g −1 at a high current density of 1700 mA g −1 (10 C), and an outstanding cycling stability over 500 cycles at 1000 mA g −1 . This excellent performance is attributed to the unique P2/P3 biphases with stable crystal structures and fast Na + diffusion between open prismatic Na sites. Moreover, operando X‐ray diffraction is applied to explore the structural evolution of Na0.67 Mn0.64 Co0.30 Al0.06 O2 during the Na + extraction/insertion processes, and the P2–P2′ phase transition is effectively suppressed. Operando Raman technique is utilized to explore the structural superiority of P2/P3 biphase cathode compared with pure P2 or P3 phase. This work highlights precisely tailoring the phase composition as an effective strategy to design advanced cathode materials for SIBs. Abstract : Co‐substituted Na x MnO2 nanosheets with tunable P2/P3 biphase structures are synthesized by a novel dealloying–annealing strategy. The optimized P2/P3–Na0.67 Mn0.64 Co0.30 Al0.06 O2 cathode exhibits excellent cycling stability and rate capacity due to the biphase synergistic effect. Operando X‐ray diffraction/Raman techniques are employed to unravel the structural evolution of prepared samples upon Na + extraction/insertion processes.